A study on the relationship between leverage and beta for the companies listed under consumer product sector of Kuala Lumpur Stock Exchange Composite Index / Salmiah Tambun - Tambun, Salmiah (1996)
This study attempt to examine the relationship between leverage and bèta with particular reference to the companies listed under the consumer products sector of the KLSE Composile Index, Ten companies were included in the sample which covers the period of six consecutive years trom 1988 to 1993. Leverage is bosed on published accounting data while bèta is taken trom Permodalan Nasional Berhad. Leverage is represented by debt ratio, debt to equity ratio, and long term debt to total asset ratio. Riskiness of the company is represented by bèta. Using the regression and corelation analysis, two alternate hypothesis were developed. First, leverage is a significant explanatory variable tor bèta. Second, bèta is dependent on leverage. In addition to the two statistical test, coëfficiënt of determination and coëfficiënt of correlotion were used to quantify the relationship between the two variables. Frorn the study, empirical findings proved that there is no significant relationship between leverage and bèta. The F-test shows that leverage is not significant in explaining the variation in bèta. Similarly, the 1- statistic test indicates that bèta is independent of leverage. Coëfficiënt of determinations show that leverage has no significant influence in bèta variation although there exists a correlotion between the two variables.